Evaluation and Governing in the 21st Century : Disciplinary Measures, Transformative Possibilities - Duffy, Deirdre Niamh (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book interrogates the role played by evaluation in 21st century governing. Using youth work in the UK as a case study, it challenges the narrative of evidence-based policy-making, arguing instead that evaluation research is used to discipline and control. At the same time, drawing on the work of Michel Foucault and Gilles Deleuze, this book argues that evaluation can be reclaimed and facilitate transformation. In bringing these theoretically rich discussions to bear on the domain of contemporary evaluation, the author provokes an alternative reading of the relationship between research and governing, emphasising how knowledge production has historically been manipulated by elites towards their own political ends. As the debate around elite's use of research expands globally, this book is a nuanced interjection into both established evidence-based policy and emergent narratives of 'post-truth'. Challenging and provocative, this innovative work will appeal to students and scholars of social and public policy, and governance and public management.- Resumé vydavatel
Keywords: evaluace -- metodologie; vládnutí -- Velká Británie; politická analýza -- Velká Británie; sociální politika -- Velká Británie; veřejná správa -- Velká Británie; evaluation -- methodology; governance -- Great Britain; policy analysis -- Great Britain; social policy -- Great Britain; public administration -- Great Britain; elektronické knihy; monografie; electronic books; monographs